Isolation and diagnosis ectoparasite from Gallinula chloropus in AL-Diwaniyah city- Iraq - Lubna abdul-kader Al-Ibrahimi .; Sadiya Aziz Anah .; Zainab Lateef Khudhair3 . (Al-Qadisiyah Journal of Pure Science, 2020)
The  current  study  aims to  revealed the   infestation  of   ectoparasites  in Moorhen Gallinula chloropus .A total of 31 Moorhen are  collected  from different areas  of Al-  Diwaniyah city -Iraq   during  the period  from March 2016  to  July  2016 .  After examination,  the  results  showed the  total  infestation   of  ectoparasites is% 87.09 , five species  of  Biting lice  are isolated . They are :Incidifrons.fulica %38.70, Menacanthus stramineus %19.35, M.cornutus %12.90,Incidifrons.sp %12.90,Geniodes. and Gigas %3.22 .